2009
DOI: 10.1186/1471-2180-9-229
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus biofilm formation at the physiologic glucose concentration depends on the S. aureus lineage

Abstract: BackgroundSince bacteria embedded in biofilms are far more difficult to eradicate than planktonic infections, it would be useful to know whether certain Staphylococcus aureus lineages are especially involved in strong biofilm formation. For this reason, in vitro biofilm formation of 228 clinical S. aureus isolates of distinct clonal lineages was investigated.ResultsAt 0.1% glucose, more than 60% of the S. aureus strains associated with multilocus sequence typing (MLST) clonal complex (CC)8 produced large amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
112
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 42 publications
18
112
0
2
Order By: Relevance
“…In contrast to our findings, they found spa type t037 (ST239-CC8-IIIA) strains form strong biofilms (Atshan et al, 2012a,b). Croes et al suggested that MLST CC8 was a predisposing factor for a strain to produce strong biofilms (Croes et al, 2009). Furthermore, the Brazilian clone (also MLST CC8) was shown to have increased adherence (Amaral et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, they found spa type t037 (ST239-CC8-IIIA) strains form strong biofilms (Atshan et al, 2012a,b). Croes et al suggested that MLST CC8 was a predisposing factor for a strain to produce strong biofilms (Croes et al, 2009). Furthermore, the Brazilian clone (also MLST CC8) was shown to have increased adherence (Amaral et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another limiting factor was not using supplementary glucose in the biofilm assay. This may influence the MRSA biofilm formation (Croes et al, 2009;O'Neill et al, 2007). Although we did analyse our collection by methicillin resistance and source of bacteraemia, these were secondary objectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some isolates, phenotypic resistance may have been caused by point mutations rather than gene acquisition. Additionally, except for the general resistance mechanisms (14), other pathways such as biofilm formation may play a major role in the resistance mechanisms (15).…”
mentioning
confidence: 99%
“…Ayrıca glukozun bakteriler tarafından kullanılması EPS ekspresyonunu artırarak biyofilm oluşumunu artırır (12). Farklı bakteri kökenleriyle yapılmış bir çalışmada yüksek glukoz konsantrasyonunun (1000 mg/dl) biyofilm oluşumunu artırdığı; yine bir çalışmada metisiline dirençli ve duyarlı Staphylococcus aureus suşlarında 250 ve 500 mg/ dl glukoz düzeylerinin biyofilm oluşumunu artırdığı in vitro olarak gösterilmiştir (13).…”
Section: Introductionunclassified